Correlation of nitrogen metabolism with biosurfactant production by Pseudomonas aeruginosa. - Mulligan, C N (1989)
A direct relationship between increased glutamine synthetase activity and enhanced biosurfactant production was found in Pseudomonas aeruginosa grown in nitrate and Proteose Peptone media. A chloramphenicol-tolerant strain showed a twofold increase in biosurfactant production and glutamine synthetase activity. Increased ammonium and glutamine concentrations repressed both phenomena.